Modulation in Ocean Primary Production due to Variability of Photosynthetically Available Radiation under Different Atmospheric Conditions. (5th January 2014) - Tripathy, Madhumita; Raman, Mini; Chauhan, Prakash; Ajai,
Abstract : The rate of photosynthesis primarily depends on nutrients and photosynthetically available radiation (PAR) at sea surface. Several ship cruises were carried out to measure optical, biological, and atmospheric parameters in the Arabian Sea and their variability were studied. An analytical nonspectral photosynthesis-irradiance model was used to estimate euphotic primary production (EuPP) to study its variability during cruise periods. PAR was estimated using COART model using in situ measured aerosol optical depth (AOD) to compare with in situ measured PAR. In order to understand the variability of PAR under different types of aerosol and different aerosol loading, a simulation study was carried out using COART model. EuPP was estimated for various PAR values under different aerosol loading and cloud coverage conditions. Sensitivity analysis showed that for maritime, maritime polluted, and desert aerosols, the ratio PAR/PAR0AOD has attenuated to about 11–25%, whereas it has attenuated to 44% for urban aerosol type. PAR/PARclear  sky was reduced by ~ 57% for high aerosol loading and for overcast sky. The decrease in EuPP under various aerosol loading and cloud coverage was observed to depend on the photoadaptation parameter. EuPP/EuPPclear  sky was reduced by 38% for maximum maritime aerosol loading and for overcast sky.